OPTIMALISASI PERAN IBU PKK KECAMATAN JOMBANG: KUNCI SOSIALISASI PENGARUSUTAMAAN GENDER UNTUK PEMBANGUNAN NASIONAL INKLUSIF - Nurhidayati, Titin; Rofiq, M. Nafiur; Hosna, Rofiatul; Rahmat, Rahmat; Salamah, Umi (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
This community service program aims to optimize the role of PKK mothers in Jombang District as the vanguard in the socialization of Gender Mainstreaming (PUG). PKK, as a grassroots organization that is in direct contact with families, has great potential to spread understanding of gender equality and inclusion in development. The problem identified is the suboptimal function of PKK education related to gender, which still tends to focus on traditional activities. The purpose of this community service program is to optimize the role of PKK mothers in Jombang District in socializing PUG to realize inclusive national development. The research method used is a participatory approach through training, workshops, and mentoring. Through training and mentoring, this program equips PKK members with the knowledge and skills to become agents of change at the local level, so that they are able to realize more inclusive and equitable national development. The expected results are increased capacity of PKK members in advocating for PUG, increased public awareness of gender issues, and active participation of women in development. The conclusion of this program is that optimizing the role of PKK mothers is an important key in the socialization of PUG at the local level, which contributes to the realization of inclusive and sustainable national development. This program is in line with local government programs related to gender mainstreaming and women's empowerment. Keywords: Gender Mainstreaming (PUG), Inclusive Development, Community Empowerment